SUBCRITICALITY ANALYSIS OF HTR-10 SPENT FUEL CASK MODEL FOR THE 10 MW HTR INDONESIAN EXPERIMENTAL POWER REACTOR - Tagor Malem Sembiring; Pungky Ayu Artiani (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2018)
The 10 MW HTR Indonesian Experimental Power Reactor (RDE reactor) is designed identical with the HTR-10 in China, conceptually. However, the review results showed that the spent fuel cask model which is used between two reactors is fully different, such as size and capacity. The proposed cask model in RDE reactor can hold 15 times more fuel pebbles than HTR-10 has. This research activities deal with the subcriticality analysis for the spent fuel cask of RDE reactor if using the HTR-10 cask model. The subcriticality condition is designed to meet the limit of safety value. The objective of this research is to determine the subcriticality value in the normal and accident events for the spent fuel cask when it is in the reactor building and the spent fuel cask room. All calculations were carried out by MCNP6.1 code. The selected external events are the water ingress (reactor room), water flood and the combination event of water flood and earthquake. The calculation results showed that the maximum value of keff (3σ) are 0.47510 and 0.19214 for the cask in the reactor building and in the spent fuel cask room, respectively. This value is far from the limit value of 0.95. The calculation results showed that the spent fuel cask are in the safe condition eventhough in the worst combination events, the cask is flooded and earthquake. The HTR-10 spent fuel cask can be proposed as an alternative for the RDE reactor to get an efficient reactor building.Keywords: spent pebble fuel element, HTGR, subcriticality, MCNP6.1, RDE reactor ANALISIS SUBKRITIKALITAS PENYIMPAN BAHAN BAKAR BEKAS MODEL CASK REAKTOR HTR-10 UNTUK REAKTOR DAYA EKSPERIMENTAL 10 MW TERMAL. Reaktor Daya Eksperimental (RDE) secara konseptual didesain identik dengan reaktor HTR-10 di Tiongkok. Meskipun demikian, terdapat perbedaan yang signifikan untuk desain konseptual cask penyimpan bahan bakar bekas di kedua reaktor seperti dimensi dan kapasitas. Kegiatan penelitian ini berkaitan dengan analisis subkritikalitas cask penyimpan elemen bahan bakar bekas tipe pebble di RDE jika menggunakan model cask yang dipakai di HTR-10. Kondisi sub-kritikalitas didesain memenuhi nilai batas keselamatan. Tujuan penelitian adalah menentukan nilai subkritikalitas dalam keadaan normal atau kondisi kecelakaan di gedung reaktor dan di gudang penyimpan bahan bakar bekas. Perhitungan dilakukan dengan paket program MCNP6.1. Kejadian kecelakaan yang dipilih adalah masuknya air ke dalam cask, cask terendam air dan kombinasi cask terendam air dan kejadian gempa. Hasil perhitungan menunjukkan bahwa nilai maksimum keff (3σ) untuk cask di gedung reaktor dan di gudang penyimpan bahan bakar bekas masing-masing adalah 0,47510 dan 0,19214. Nilai ini masih jauh dari batas 0,95. Hasil perhitungan menunjukkan bahwa cask penyimpan bahan bakar bekas tetap dalam keadaan selamat meski terjadi kombinasi 2 kejadian eksternal.Kata kunci: elemen bahan bakar bekas tipe pebble, HTGR, subkritikalitas, MCNP6.1, RDE